Programa de atenção a homens autores de violência contra a mulher: possibilidades a partir da vivência de casais em situação de violência conjugal - Flavia Gotelip Correa Veloso (2011)
The law 11.340/06 (Maria da Penha Law), while creates mechanisms to restrain and prevent domestic and intrafamily violence against women provides the implemetation of the Accountability and Batterer Education Programs. In this context, we identified the importance of analyzing the marital dynamics and the dynamics of violence experienced by women and men in intimate partner violence, before, during and after the man's participation in a batterer reflexive program, aiming to understand the contributions and limits of the program for the confrontation and prevention of the violence they had experienced. With this objective, we interviewed four women and four men, among which were 3 couples, that the men participated in Batterer Programs, developed by the Kernel of Psychosocial Support to the Family in Situation of Violence linked to the Police Department of Women, Child, Adolescent and Elderlys Protection in the city of Divinópolis/MG. The information was subjected to the phenomenological method for psychological investigation and reorganized into narratives that attempt to identify the particularities and the common points in the experiences reported. The results point to four divergent central axis among the male and female subjects: 1) insights about the dynamics of violence in the marital dynamics; 2) perceptions about marriage and the motivations for its end; 3) perception about reporting the violence; 4) perception about the group for battered men. In the womens speeches it is noted that: women gave details of the episodes, contexts and types of violence experienced in conjugal dynamics; the representations of marriage point to the "couples happiness" tied to the ideal of romantic love, taking them to wait for changes in the partners behavior, postponing the end of the relationship; the act of reporting is seen as "to send to prison", so they choose not to record the police occurrence of the facts, preferring the referral of the author to the Group; and the group for the men is a "treatment" that little contributed for the confrontation of the situation of violence lived by the female, which does not mean for them that it cannot be beneficial in other cases. The men however do not admit the history of violent conjugability but recognize the aggressive acts that generated the referral to the Group; the marriage representation relates to the family happiness and does not make the conflict conjugability a motivation to its end; the act of reporting is seen as shameful for the man but after being filed in the police station it is understood as a request for help from the woman and not necessarily an attempt to harm him; and the battered group represents a learning-school which means a place to learn self control. From these experiences, we observe the permanence of traditional genre representations that maintain and legitimize the conjugal hierarchy and the practice of violence, without that assistance offered to parties to promote the female empowerment and the rupture of the values of hegemonic masculinity of men. We highlight the need of programs for men to become effective as a genre public policy inserted into a network of services directed to all those involved in the dynamics of conflict.